SIA dan Kepatuhan terhadap PSAK/IFRS dalam Lingkungan Digital : Sebuah Studi Literatur - Syarifah Ghizka Safitri; Mawardahny Isyabilla; Norbert Nathanael Saragih; Jumiadi AW (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of Accounting Information Systems in supporting entities’ compliance with Financial Accounting Standards converged with the International Financial Reporting Standards in the context of digital business. Using a qualitative method and a literature review approach, the study examines the function of Accounting Information Systems, the impact of standard convergence on financial reporting quality, and the challenges of implementation. The findings indicate that Accounting Information Systems enhance efficiency, accuracy, and internal control, which are essential for accounting compliance. The convergence of standards has been shown to strengthen the relevance of information, although its influence on earnings management remains varied. The study also reveals challenges such as technological limitations, low accounting literacy, and resistance to change. Successful implementation requires strategic synergy among regulators, business entities, and accounting professionals.